Histopathological Features Analysis of Sarcoidosis in Different Organs - Ma, Ziyuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Sarcoidosis is a complex inflammatory disease involving many systems and its exact cause is still unknown. The characteristic in histopathology of it is the occurrence of epithelioid cell granulomas. The most common type of lymph node involvement is the lungs and chest has risks of other organs. Common diagnostic methods rely on clinical symptoms, imaging, and histopathology. Histopathology is the microscopic study of tissues affected by a disease and is essential for diagnosing sarcoidosis and differentiating it from other granulomatous disorders. According to different affected organs, the histologic pattern of sarcoidosis is also different. Lungs is the most affected organ. Granulomas are usually found within the interstitium, often with varying degrees of fibrosis. Cutaneous manifestations include a range of lesions such as erythema nodosum and lupus chilblain, and histological test may present dermal granulomas and lymphocytic infiltrates. Although liver involvement usually asymptomatic, its characteristics is a portal with a triple granuloma, occasionally accompanied by mild portal inflammation. This paper aims to investigate the histopathological findings of sarcoidosis in different organs.